TiO(2) Coating and UV Photofunctionalization Enhance Blood Coagulation on Zirconia Surfaces - Shahramian, Khalil (Biomed Res Int, 2019)
This in vitro study was designed to evaluate the effect of sol-gel derived TiO(2) coating on blood coagulation, blood protein adsorption, and platelet response on zirconia surfaces. Square-shaped zirconia (n=96) (10x10x2 mm) was cut, ground, sintered, and finally cleansed ultrasonically in each of acetone and ethanol for 5 minutes. Three experimental groups (n=32) were fabricated: (a) zirconia coated with sol-gel derived TiO(2), (b) zirconia coated with sol-gel derived TiO(2) and treated with ultraviolet (UV) irradiation for 1 hour, and (c) non-coated zirconia as control. The coatings were prepared from tetraisopropyl orthotitanate solution by dip-coating. The thrombogenicity of the specimens was evaluated using a whole blood kinetic clotting time method where the extent of blood clotting was evaluated at 10, 20, 30, 40, 50, and 60 minutes (n=4/time point, total n=24/group). Scanning electron microscope images were taken to observe platelet morphologies after 1-hour incubation with platelet-rich plasma (PRP) (n=5/group). Surface characteristics were visualized using atomic force microscopy (n=1/group). Adsorption of plasma proteins and fibronectin on each surface was studied by gel electrophoresis (n=2/group). Significant differences were observed in blood coagulation between the test groups at 20-, 30-, 40-, and 50-minute time points (p<0.005). UV treated TiO(2) coated specimens showed fastest blood coagulation followed by TiO(2) coated and non-coated specimens. Furthermore, platelets appeared at a higher activation state on coated specimens. Gel electrophoresis revealed no difference in protein adsorption among the experimental groups. In summary, TiO(2) coatings promoted blood coagulation, and it was further enhanced by UV treatment, which has the potential to hasten the wound healing process in vivo.